Outcome Evaluation of the Wisconsin Residential Substance Abuse Treatment (RSAT) Program: The Mental Illness Chemical Abuse (MICA) Program at Oshkosh Correctional Institution, 1997-2000 - Moberg, D. Paul ([Verlag nicht ermittelbar], 2003)
This study evaluated the Mental Illness-Chemical Abuse (MICA) Program at Oshkosh Correctional Institution in Wisconsin. MICA is a residential substance abuse treatment program that consists of three stages: (1) an 8- to 12-month residential therapeutic community stage, (2) an institutional aftercare stage, and (3) a community aftercare stage. This outcome study documented important aspects of program implementation and effectiveness. It included all 141 inmates admitted to MICA between October 1997 and March 2000. A control group comprised of 66 inmates who were too close to their mandatory release dates to participate in the program but who were otherwise eligible was also included. Data were gathered from Department of Corrections administrative records regarding admissions information, assessment results, institutional behavior, institutional placement and services after program completion or exit, and recidivism. MICA staff provided information on treatment progress, behavior, and mental health status. MICA outreach specialists provided three-month post-release data on community outcomes for MICA graduates. Parole agents provided three-month post-release data on parole compliance and recidivism for all study participants. Variables include assessment results, institutional services received, history of incarceration, urinalysis testing, changes in mental health status and program behavior throughout treatment, clinical test results, conduct reports, institutional placement and services after MICA, whether the individual had appropriate resources upon release to the community, parole status, recidivism, mental health and chemical use status after release, support services provided by MICA staff after release, and other support services received after release.